Hi there,

First off I'm new to java and coding in general so please bear with me. I'm trying to write a bit of code that will convert something like the following
con(pk(B),pk(AS),pk(A),B)
to this
k_B, k_AS, k_A, B

I have written the following code :

Pattern pk = Pattern.compile("pk(.*)"); //Regular Expression Pattern

int varsLen = initialVars.length();
String[] elements = initialVars.split(","); //Split up the terms
for (int x=0; x<elements.length; x++) {
Matcher m = pk.matcher(elements[x]); //match array element
boolean b = m.matches(); //Does array element match
if (b) { //If there is a match
pkStart = elements[x].indexOf("pk(", pkEnd) + "pk(".length();
pkEnd = elements[x].indexOf(")",pkStart);
elements[x] = elements[x].substring(pkStart,pkEnd);
csPrelimOut = "k_"+elements[x];
csOut = csOut.concat(csPrelimOut);
} else {
csPrelimOut = elements[x];
csOut = csOut.concat(csPrelimOut);
}

}
csOut = csOut.replace(' ',',');

When I use this code it always works for the first element of the array but not the remaining elements. I'd get k_B from pk(B), but for the remaining pk() elements i'd just get them reiterated e.g. pk(AS) would remain pk(AS). I've never used regular expressions before so maybe that's where I'm going wrong. From "Pattern pk = Pattern.compile("pk(.*)");", I mean to set up a regular expression that starts with "pk(", then can be followed by 1 or more characters, and finally ended with ")". Does anyone have any idea how I might sort this out? Thanks a million.